Interaction of a peptide derived from C-terminus of human TRPA1 channel with model membranes mimicking the inner leaflet of the plasma membrane - Witschas, Katja; Jobin, Marie-Lise; Korkut, Dursun Nizam; Vladan, Maria Magdalena; Salgado, Gilmar; Lecomte, Sophie; Vlachova, Viktorie; Alves, Isabel D (Biochimica et biophysica acta, 2015)
The transient receptor potential ankyrin 1 channel (TRPA1) belongs to the TRP cation channel superfamily that responds to a panoply of stimuli such as changes in temperature, calcium levels, reactive oxygen and nitrogen species and lipid mediators among others. The TRP superfamily has been implicated in diverse pathological states including neurodegenerative disorders, kidney diseases, inflammation, pain and cancer. The intracellular C-terminus is an important regulator of TRP channel activity. Studies with this and other TRP superfamily members have shown that the C-terminus association with lipid bilayer alters channel sensitivity and activation, especially interactions occurring through basic residues. Nevertheless, it is not yet clear how this process takes place and which regions in the C-terminus would be responsible for such membrane recognition. With that in mind, herein the first putative membrane interacting region of the C-terminus of human TRPA1, (corresponding to a 29 residue peptide, IAEVQKHASLKRIAMQVELHTSLEKKLPL) named H1 due to its potential helical character was chosen for studies of membrane interaction. The affinity of H1 to lipid membranes, H1 structural changes occurring upon this interaction as well as effects of this interaction in lipid organization and integrity were investigated using a biophysical approach. Lipid models systems composed of zwitterionic and anionic lipids, namely those present in the lipid membrane inner leaflet, where H1 is prone to interact, where used. The study reveals a strong interaction and affinity of H1 as well as peptide structuration especially with membranes containing anionic lipids. Moreover, the interactions and peptide structure adoption are headgroup specific.
Keywords: Protein Structure, Tertiary; Hydrogen-Ion Concentration; Phase Transition; vazba proteinů; vápníkové kanály; Anisotropy; terciární struktura proteinů; Structure-Activity Relationship; lidé; membrány umělé; Buffers; Transient Receptor Potential Channels; Calcium Channels; Membrane Lipids; Membranes, Artificial; proteiny nervové tkáně; peptidové fragmenty; Nuclear Magnetic Resonance, Biomolecular; Protein Structure, Secondary; Nerve Tissue Proteins; sbalování proteinů; Peptide Fragments; nukleární magnetická rezonance biomolekulární; Protein Folding; anizotropie; sekundární struktura proteinů; změna skupenství; vztahy mezi strukturou a aktivitou; pufry; buněčná membrána; koncentrace vodíkových iontů; Protein Binding; membránové lipidy; kationtové kanály TRP; Cell Membrane; Humans